Abordagem metodológica para a valuação do petencial desregulador endócrino de água de beber: estudo com amostras reais - Solano, Marize de Lourdes Marzo [UNESP] (2014)
If contaminated waters are treated by conventional processes (WTP) emerging contaminants are not fully removed and will remain in the drinking water (DW). We investigated the potential for endocrine disruption of two DW samples collected in 2010 and 2012 from a WTP located in São Paulo, Brazil. Water samples were extracted and chemically analyzed for emerging substances and evaluated with an in vitro bioluminescent yeast assay containing estrogen/androgen human receptors (BLYES/BLYAS). In vivo assays were conducted with 21-day old female rats exposed to DW extracts for 03 (uterotrophic assay; OECD) or 20-days (pubertal assay, EPA). The exposure represented a daily ingestion of 2 L, 5 L and 10 L of DW by a 60 kg human being. Caffeine (5.8 - 21 ug/L), estrone (1 ng/L), atrazine (2.2 -11.2 ng/L), carbendazim (0.22 ng/L), azoxistrobina (0.23 ng/L) and tebuconazole (0.19 ng/L) were detected in DW by LC-MS/MS-ESI. There were no increase of the uterus wet weight in the uterotrophic assay, and no alteration of the vaginal opening moment in the pubertal assay. However, there was increased relative blotted uterus weight in animals treated for 3-days with both DW. Levels of LH and FSH presented a significant dose-response increase in the uterotrophic assay developed with the 2010 sample. This happened in association with a significantly increased incidence of vaginal keratinization after the 3-day exposure. Results suggest the DW tested exerted hypothalamic-hypofisis activity alteration in vivo. Additional end-points in standard protocols could be useful to evaluate the presence of endocrine disruptor activity in DW